Los „zakazanych książek” w Bibliotece Uniwersyteckiej w Poznaniu - Góra, Barbara (Biuletyn Historii Wychowania, 2016)
This article presents and examines the fate of prohibited and condemned books in Communist Poland in the years 1945–1989 held at the time in Poznań University Library. The subject is addressed based on available archive records, ordinances and decrees passed by the Communist authorities, as well as on in-house regulations, internal instructions, reports and relevant documents issued by the Head Librarian.